Exploring the relationship between cultural ecosystem services and human well-being of Qiandao Lake in China: insights from tourists and residents - Jie Wang; Kuan Wang; Shuangjin Li; Huiyong Song; Shuang Ma; Weiwu Han; Di Pang (Environmental Research Communications)
Landscapes of lakes have a significant impact on people’s perceptions of Cultural Ecosystem Services (CES), as well as on their overall sense of well-being. However, there is limited understanding of how best to manage land landscapes and how different approaches influence these perceptions. To explore these questions, a case study of China’s Qiandao Lake was conducted, using a survey of 416 tourists and residents based on the Millennium Ecosystem Assessment (MA) framework. The relationship between CES and Human Well-Being (HWB) was examined using Structural equation Modeling (SEM), followed by the application of the Importance-Performance Analysis (IPA) method to identify which aspects should be targeted in management strategies. The results revealed several key findings. Firstly, there were significant differences in satisfaction with CES between tourists and residents. Tourists showed higher satisfaction levels in spiritual service, aesthetic service, inspiration, and education and science aspects. In contrast, residents prioritized cultural heritage and sense of place, indicating a deeper connection to the cultural and historical elements of their environment. Secondly, age, education, and income levels played important roles in shaping perceptions of CES. Thirdly, the study underscored the impact of CES on HWB, with aesthetic service having the greatest influence on tourists’ HWB, and spiritual service having the most impact on residents’ HWB. Lastly, using the IPA model, indicators with low satisfaction but high importance were identified, suggesting areas for improvement, particularly in cultural integration and unique environmental features. These research findings provide scientific and theoretical support for the management and landscape planning of lake ecosystems.